PERAN DOKTER FORENSIK DALAM MEMBANTU PENANGANAN PERKARA PIDANA - Gunawan Widjaja; Muthia Rachman (JOURNAL OF LAW AND NATION, 2022)
Handling criminal cases often requires assistance from other sciences. One of them is forensic medicine. This study aims to discuss the role of forensic doctors in assisting the settlement of a criminal case. This research is a normative legal research that prioritizes the use of primary legal materials with a qualitative approach. The discussion and analysis shows that there are many roles that can be performed by forensic doctors. This can be found in the recognition that has been given in various applicable laws and regulations.